Egg Incubator Control System: A Review - Zakaria, Diky; Hamzah, Muhammad Bilal; Nazhif, Dany Syauqi; Prayudha, Rezka Bunaiya; Wahid, Muhammad Rizalul; Ramelan, Agus; Muttaqin, Muhammad Husni; Nugraha, Adi (Universitas Sebelas Maret (UNS), 2023)
Chicken or duck farming is one of the businesses that has good prospects. Conventional hatching of chicken or duck eggs has its own risks with a hatching success percentage of <81%. The hen or duck also needs time for further breeding because they have to incubate the eggs first. Egg incubators on the market usually use on-off controls to regulate incandescent lights which can cause the temperature to fluctuate. Air humidity settings are also manually set by the user. Researchers have conducted studies related to temperature and humidity settings. This article reviews articles from the Scopus database related to control systems in egg incubator with research questions: controlled parameters, sensors used, control theory, methods, and research results that have been carried out. The result of this article can provide an overview of the research development related to egg incubator control systems.